P485Re-interpretation of variants of uncertain significance in inherited cardiovascular diseases-A pilot study. (18th June 2020) - Novelli, V; Mazza, D; Cammarano, M; Quarta, R; Curra, M; Zeppilli, P; Crea, F; Tiziano, F D; Genuardi, M
Abstract: Background- Identification of variants of uncertain signiﬁcance (VUSs) poses relevant challenges in counseling and managing patients. They have an unknown impact on health, making the genetic tests clinically irrelevant. Recent studies demonstrate that a routine reclassification analysis enables to reclassify from 20% to 80% of this type of variant, improving risk stratification. Purpose- We investigated whether, in the context of inherited cardiac conditions, a review of the updated literature, including new functional data, allele frequency (GnomAD) and segregation analysis may help in the variant reclassification. Methods- Retrospective review of all VUSs in genes associated with inherited cardiac conditions identified in our cardiogenetic clinic between 2016 and 2018. Results- Thirty-one VUSs, classified using ACMG guidelines, were identified in 26 cases with a confirmed or suspected diagnosis of inherited cardiovascular diseases, including Long QT syndrome, Brugada syndrome, Arrhythmogenic Cardiomyopathy and Hypertrophic Cardiomyopathy). Twentyfour variants were identified in well-defined causative genes (SCN5A, KCNQ1, KCNH2, KCNE1, DSP, DSG2, MYH7, TPM1, TNNI3, TNNT2, CACNA1C, MYL3) while the remaining variants were identified in minor genes with limited evidence to support their disease causation as, ANK2 and AKAP9 gene. Preliminary results of the reclassification analysis showed that two variants were downgraded to likely benign (LB) applying the BS1 criterion (allele frequency) and 4 variants were upgraded to likely pathogenic (LP) according to novel published data and family segregation studies. Moreover, further studies to assess cosegregation in other variants are still ongoing. Conclusion- Based on our experience, 25% of variants of uncertain significance in well-defined causative genes, identified in patients with a confirmed or suspected diagnosis of inherited cardiovascular disease, were reclassified. These findings suggest that re-evaluation of genetic test results should be performed routinely in all diagnostic labs, in order to improve risk stratification and identification of family members at high risk.